2021
DOI: 10.1590/1414-431x2021e11232
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circulating follicular regulatory T cells in patients with dilated cardiomyopathy

Abstract: Follicular regulatory T cells (Tfr) have critical functions in inflammatory and autoimmune disorders. The main purpose of the current work was to assess Tfr cell frequency in patients with dilated cardiomyopathy (DCM). Flow cytometry showed that, compared with normal controls, DCM cases showed markedly reduced Tfr cell rates and Tfr/Tfh ratios, but significantly increased follicular helper T cell (Tfh) rates. Correlation analysis showed that the Tfr rate in DCM patients was positively correlated with left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Additionally, Zhao et al [ 18 ] reported that COL1A2 may participate in DCM pathogenesis by regulating the cardiac remodeling characterized by collagen deposition in the extracellular matrix[ 56 ]. Consistent with our results, Liu et al [ 53 ] identified STAT3 as a hub gene in DCM via bioinformatic analysis. Other studies have also indicated a role of STAT3 in DCM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, Zhao et al [ 18 ] reported that COL1A2 may participate in DCM pathogenesis by regulating the cardiac remodeling characterized by collagen deposition in the extracellular matrix[ 56 ]. Consistent with our results, Liu et al [ 53 ] identified STAT3 as a hub gene in DCM via bioinformatic analysis. Other studies have also indicated a role of STAT3 in DCM.…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al [ 52 ] reported that elevated IL-17 levels are significantly associated with DCM incidence and progression. Additionally, the serum levels of other inflammatory factors such as IL-6, tumor necrosis factor-α, and IL-21 are significantly increased in DCM patients[ 53 ]. Thus, the IL-17 signaling pathway may be one of the major signaling pathways involved in the development of DCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is been reported that polarization of macrophages towards M2 was associated with ventricular remodeling and poor long-term prognosis in DCM ( Nakayama et al, 2017 ). In addition, a significant increase of the number of Th1 and Th17 cells was observed while the number of Treg cells decreased in DCM patients ( Wei et al, 2017 ; Liu et al, 2021 ). Infiltrated immune cells release cytokines and chemokines, such as TGF-β1, IL-1β, and TNF, promoting collagen deposition, fibrosis and cardiac remodeling ( Schultheiss et al, 2019 ).…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, histone peptides have also been shown to have immunosuppressive activity by activating a subtype of T reg, named follicular regulatory T cells (T frs ) (CXCR5 high PD-1 high and FoxP3 + ), which are located in B cell follicles of secondary lymphoid organs. T frs play pivotal roles in regulating B cell responses and inhibiting the development of auto-Ab ( 88 91 ). Histones and nuclear proteins have been shown to induce T frs expansion and up-regulation of immunosuppressive genes ( 92 ).…”
Section: Translational Therapeutic Applications: Conventional and Reg...mentioning
confidence: 99%